THE EFFECT OF USING THE QUIZIZZ APPLICATION ON STUDENTS’ VOCABULARY MASTERY - Agustin, Natasya Tania (Department of English Education, Universitas Panca Sakti Bekasi, 2022)
The aim of this research is to know how the effect of the Quizizz application on students’ vocabulary mastery at 7th grade of SMPN 6 Bekasi. This research method uses an experimental design. The sample is all students of VII-G and VII-H 7th grade of SMPN 6 Bekasi. This data was obtained by conducting a post-test on the students. The results of the attached t-test table, it is known that the value of Sig. (2-tailed) < 0.5. By equating the score of the experimental class with the score of the control class, the experimental class is greater than the score of the control class. Based on the analysis of information, it’s known that students in grades VII-G who use Quizizz to increase their learning motivation in English vocabulary mastery have a higher level of total English vocabulary knowledge. This shows that the t-test value has a significance level. In other words, Quizizz has an effect on increasing vocabulary mastery and motivation for students.